2012
DOI: 10.4274/turkderm.79653
|View full text |Cite
|
Sign up to set email alerts
|

Alopesi Areatada Stresin Rolü ve Hastaların Yaşam Kalitesinin Androgenetik Alopesi ve Sağlıklı Kontrollerle Karşılaştırılması

... ...

Abstract: ÖzetAmaç: Emosyonel stresin alopesi areatayı tetiklediği henüz net olarak gösterilmiş değilse de nöroendokrinolojik çalışmalar psikolojik stresin hastalık sürecinde etkili olabileceğini desteklemektedir. Bu çalışmada alopesi areatanın başlangıcı ve alevlenmesinde stresli yaşam olaylarının rolünü ve alopesi areata hastalarında anksiyete, depresyon ve yaşam kalitesi düzeylerini androgenetik alopesi ve sağlıklı kontrol grubu ile karşılaştırarak ortaya koymayı amaçladık. Gereç ve Yöntem: Alopesi areata tanısı alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Areata and mental symptoms have indicated that the Beck Depression Inventory scores of individuals diagnosed with Alopecia Areata are significantly higher when compared to the control groups, but the evidence is lacking about the direction of the cause-effect relationship between the two (Arı et al, 2011;Arpağ et al, 1999;Şahin et al, 2008;Sellami et al, 2014;Yaylı et al, 2012). The aim of the present study was to examine the relationship between Alopecia Areata and depression, as well as the quality of the early object relations of Alopecia Areata patients.…”
Section: Discussionmentioning
confidence: 99%
“…Areata and mental symptoms have indicated that the Beck Depression Inventory scores of individuals diagnosed with Alopecia Areata are significantly higher when compared to the control groups, but the evidence is lacking about the direction of the cause-effect relationship between the two (Arı et al, 2011;Arpağ et al, 1999;Şahin et al, 2008;Sellami et al, 2014;Yaylı et al, 2012). The aim of the present study was to examine the relationship between Alopecia Areata and depression, as well as the quality of the early object relations of Alopecia Areata patients.…”
Section: Discussionmentioning
confidence: 99%